The effect of foot orthoses for patients with patellofemoral pain syndrome: A systematic review and meta-analysis. Issue 6 (June 2022) - Chen, Ziyan; Wu, Jinlong; Wang, Xiaodong; Ren, Zhanbing
Abstract: Objective: This research quantitatively studied the benefits of foot orthoses for patients with patellofemoral pain syndrome (PFPS) from five aspects: pain intensity, knee function, sport and recreation function, knee symptoms, and knee related quality of life. Data sources: Potential articles were retrieved using five electronic databases (Web of Science, PubMed, Scopus, China National Knowledge Infrastructure, and Wanfang). The search period was from inception to October 17, 2021. Review methods: Two researchers independently completed record retrieval and selection, data extraction, and methodological quality assessment. Pooled effect sizes were calculated using a random-effects model or fixed-effect model and a 95% confidence interval (95% CI). Data from six randomized controlled trials (RCT) meeting the inclusion criteria were extracted for meta-analysis with methodological quality assessment scores ranging from seven to ten. Results: Results showed that compared to the control group, foot orthoses can significantly improve knee function (SMD = -0.45[-0.74, -0.16], P = 0.002, I 2 = 0%), and improve sport and recreation function (SMD = -0.54[-1.04, -0.03], P = 0.04, I 2 = 0%). But the foot orthoses had no significant effect in pain intensity (SMD = -0.01[-0.32, 0.30], P = 0.95, I 2 = 64), knee injury symptoms (SMD = -0.36[-0.86, 0.14], P = 0.16, I 2 = 0%), and knee related quality of life (SMD = -0.45[-0.95, 0.05], P = 0.08, I 2 = 0%). Subgroup analysis of pain intensity showed that foot orthoses had some effect compared to flat/soft inserts (SMD = -0.28[-0.57, 0.00], P = 0.05, I 2 = 0%). The effect of other treatments (physiotherapy and gait retraining) was significantly better than that of foot orthoses (SMD = 0.45[0.09, 0.80], P = 0.01, I 2 = 46%). Compared with exercise alone, the effect of foot orthoses combined with exercise was more significant (SMD = -0.98[-1.64, -0.32], P = 0.004). Conclusion: The findings suggested that foot orthoses significantly improved knee function and sport and recreation function in patients with PFPS, but had no significant effect on pain intensity, knee injury symptoms, and knee related quality of life. This study supported the positive therapeutic effect of foot orthoses on PFPS. Abstract : Foot orthoses; Patellofemoral pain syndrome; Knee function; Pain intensity; Systematic review; Meta-analysis.